Use of Game Technologies in the Process of Physical Education and Healthcare of 6-7 Year Old Children in Preschool Educational Organizations - Ibragimova Lola Asatullayevna; Ziyatov Muhammad Namazovich; Hamdamova Mavsuma Pardaboy qizi (Researchparks Publishing, 2022)
Forms of play play an important role in the types of activities in preschool education, because play activities are in line with the nature of the child. Along with not only fun games for children, but also a method of modeling the outside world, the adult world, modeling relationships in society, in the process develops a scheme of relationships with children's peers. Special attention is paid to the development of coordination skills, such as crawling, throwing, hanging, mastering the basic types of movement and the formation of correct techniques . Today, the most common way to develop this type of movement is to repeat the exercise (walking or moving around in a circle, performing exercises as a group or individually, throwing and catching the ball, etc.).